Friedberg numberings in the Ershov hierarchy - Badaev, S. A.; Mustafa, M.; Sorbi, Andrea (Springer, 2014)
We show that for every n 1, there exists a 􀀀1n -computable family which up to equivalence has exactly one Friedberg numbering which does not induce the least element of the corresponding Rogers semilattice.
Keywords: minimal numberings